A Patient with Concurrent Legionella and COVID-19 Infection in a UK District General Hospital. (24th November 2022) - Tong, Jie L.; Long, Michael A.; Russell, Peter
Abstract : A 65 year-old gentleman had been brought to our Respiratory Emergency Department for patients with respiratory symptoms and a possible COVID-19 infection with a 3-day history of shortness of breath (SOB), fever, a productive cough of yellow sputum, and right-sided chest pain. The patient had received both vaccinations at the time and initially reported no travel history, although later it was revealed that he had recently stayed at a hotel. He tested positive for COVID-19 and had hyponatremia and a raised procalcitonin, indicating a bacterial infection as well. He had been initiated on our local treatment guidelines for COVID with antibiotics, guided by local hospital guidelines. An atypical pneumonia screen returned a positive result for Legionella urine antigen, and his antibiotic regime was changed accordingly. Our patient deteriorated significantly, and despite being escalated to our intensive care unit (ICU), he unfortunately passed away. Our case highlights the importance of early ICU involvement and escalation of antibiotics in cases of suspected concurrent Legionella and COVID-19 infections.